2022
DOI: 10.1177/07399863221116849
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Attitudes Toward Roe v. Wade Among US Latinx Adults

Abstract: This study examines knowledge of and attitudes toward Roe v. Wade among a sample of 779 US Latinx adults. Survey response patterns were examined in relation to generational status and choice of survey language as well as to several demographic variables previously shown to influence abortion attitudes (e.g., age, religiosity, political affiliation). Differences were found in knowledge of Roe v. Wade by generational status and survey language, with those with higher generational statuses and those taking the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Dobbs v. Jackson and subsequent state-level abortion bans have evoked strong reactions from “pro-life” and “pro-choice” groups [ 4 ]. Many studies on attitudes towards Roe v Wade have used surveys [ 10 , 11 ]. However, much of the public reaction to Dobbs v. Jackson has been expressed on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Dobbs v. Jackson and subsequent state-level abortion bans have evoked strong reactions from “pro-life” and “pro-choice” groups [ 4 ]. Many studies on attitudes towards Roe v Wade have used surveys [ 10 , 11 ]. However, much of the public reaction to Dobbs v. Jackson has been expressed on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Also, because Twitter demographic data does not include race, it was not possible to examine how sentiments and topics varied by race/ethnicity which could have been valuable to the findings in this study. Second, this study only used tweets posted in English language thus leaving out a proportion of tweets expressed in other languages (for example, Spanish), especially with the growing population of Latinx population in the US ( 50 ) which would have generated findings relevant to the conclusions in this study. A third limitation is related to the keywords used to retrieve Roe vs. Wade related tweets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, public attitudes toward abortion are related to a variety of factors, including religion, gender, stigma, political affiliation, and socioeconomic status (Mosley et al 2020;Patev, Hood, and Hall 2019). Recently, some questionnaires and user studies examined attitudes toward Roe v. Wade (Solon et al 2022;Crawford et al 2022). They found that more participants supported Roe v. Wade than opposed it, while greater knowledge about Roe v. Wade was correlated with larger support for maintaining it.…”
Section: Introductionmentioning
confidence: 99%